HALAL AWARENESS: IMPACT ON PURCHASING HALAL MEDICINES UNVEILED - Al Maslul, Syaifullah; Priantina, Anita (Bank Indonesia, 2024)
Indonesia offers significant opportunities for the halal sector thanks to its predominantly Muslim population. However, there is a notable lack of certified halal medicines, which is surprising given the crucial role that medicines play in human life. This study aims to investigate how awareness of halal practises influences Muslim consumers' intention to purchase halal medicines, with a particular focus on the Jabodetabek region. The study is based on a total of 150 respondents and employs a partial least squares structural equation modelling (PLS-SEM). From the analysis, it is found that awareness of halal products has a significant influence on the intention to purchase halal medicines. In addition, both subjective norms and perceived behavioural control are identified as significant factors influencing the intention to purchase halal medicines. However, it is worth noting that attitude does not have a statistically significant influence on the intention to purchase halal medicines. This result may be attributed to the limited availability of halal-certified medicines, which influences the attitude of individuals in the decision-making process.